Aplikasi Deteksi Orang Jatuh dengan Memanfaatkan Kinect - Jonathan Tjitrokusmo; Liliana Liliana; Kartika Gunadi (Jurnal Infra, 2017)
This paper describes method for fall detection, because fall is a serious problem and often resulting to injury, which can endanger the safety of the person. Therefore, falling detection is crucially needed. The device that being used is Kinect, which also could be used to detect people. The detection is using the help of Microsoft Kinect SDK. Kinect can detect a person in front of it and processing it to create a skeleton of the person. The method which being used is to get a set of data on the position of the person. Next, the rate of change in position would be calculated with the available formulae. The data obtained would be selected, in order to distinguish the activities undertaken. When fall is detected, the application can provide the alert.